Implementation of village heads' neutralism in the General Election Campaign based on Law Number 6 of 2014 concerning Villages - Angkasa, Nitaria; Pelangi, Intan (Universitas Muhammadiyah Metro, 2024)
Based on village authority which is a form of village government, the village head has a role in the splendor of the democratic party in Indonesia which will be held on February 14 2024, but the role of the village head is so important as the head of the village government, it is necessary to study the head's neutrality. villages in general election campaigns and regional head elections in Indonesia. The method used in this research is normative juridical. The method used in carrying out the research is carried out by collaborating in the form of data and field facts. The problem approach used in this research is normative. The neutralistic implementation of village heads based on the election law and village law in elections shows that the Division for Handling Violations of the Election Supervisory Agency (Bawaslu) of DKI Jakarta Province, Benny Sabdo, emphasized that the campaign activities of election participants are prohibited from involving the State Civil Apparatus (ASN) and village heads and factors. The basic thing about the neutrality of village heads in elections is that there is concern that there will be a conflict of interest between village officials and the community and this is also regulated in Law Number 7 of 2017 concerning elections in Article 20 Paragraph 2 which states that village officials are among the parties who are prohibited from being included by the implementer or team. campaign in election campaign activities. The prohibition on village officials from taking part in practical politics is also contained in Law no. 6 of 2014 concerning Villages, Article 29 letter g states that village heads are prohibited from being administrators of political parties and in letter j village heads are prohibited from participating and/or being involved in election campaigns and/or Pilkada. Village officials are advised not to get involved in political activities, either as cadres and campaign activists.